Rheological properties of blended metakaolin self-compacting concrete containing recycled CRT funnel glass aggregate - Ouldkhaoua, Y; Benabed, B; Abousnina, Rajab; Kadri, E (2019)
Rheology is a field of fluid mechanics that studies the flow of materials and the interaction between stress states and deformation according to their viscosity, elasticity and plasticity and with the appearance of new materials and the complex behaviour of concrete pumpability, since the field of civil engineering is interested in the study of concrete flow. This work will examine how the use of catodique ray tube (CRT) glass as sand replacement in proportions of 0, 10, 20, 30, 40 and 50%, and metakaolin (MK) powder in proportions of 5, 10 and 15% will affect the rheological properties of self-compacting concrete (SCC). In this investigation, the flow ability of SCC was evaluated by slump flow, L-Box, and V-funnel tests. Its resistance to segregation was measured by the sieve stability test and the yield stress and plastic viscosity was determined by a modified slump test. This investigation concluded that CRT glass improved the rheological properties and minimised the dosage of superplasticiser (SP); the best results came from concrete with 50% of CRT sand glass. This improvement helps to overcome the negative effect of MK in SCC pumpability and reduces the time of casting. An acceptable relationship between rheological properties shows that a modified slump test can be used to evaluate yield stress and viscosity. Keywords: CRT, metakaolin, rheological properties, self-compacting concrete Kulcsszavak: CRT, metakaolin, reológiai tulajdonságok,